Observation of Wild Seaweed Species in Labuhanbua Waters, Indonesia: a preliminary assessment for aquaculture development - Erlania Erlania; I Nyoman Radiarta (Journal Omni-Akuatika, 2017)
Seaweed industry has been growing up and is supplied by either wild or cultivated seaweed crops. This study was aimed to present relevant information regarding ecological availability of wild seaweed in Labuhanbua coastal waters, Sumbawa Regency, West Nusa Tenggara and potential use of important species as candidate species for aquaculture. 46 sampling stations were determined along line transects perpendicular to coastal line; and seaweeds sampling were conducted during low tide by using 1 x 1 m2 quadrat transect. Field data consist of in-situ parameter including number of seaweed species and coverage area of each species; and ex-situ parameters consist of carbohydrate, protein, total C, total N, and total P content of seaweeds. The results showed that 33 species were found and three species has the most widely distribu tion, i.e. Padina sp., Dictyota dichotoma, and Gracilaria salicornia. Turbinaria, Dictyota, Padina, Stoechospermum, Hydroclathrus, Halimeda, and Chaetomorpha might be some important species that could be develop as aquaculture species candidates among other uncultivated species that were found along this study location. They have potencies as human food, livestock feed, neutraceuicals, cosmetics, pulp, textile, biofuel and any other industries; but conversely, they were found in lower density at Labuhanbua coastal waters. These species should be develop through aquaculture technology, involve genetic improvement and possibly genetic engineering. Commercial scale cultivation of those important seaweed species will contribute to industrial needs and prevent decreasing of wild seaweed availability in natural ecosystem.